SOSIALISASI MODEL PEMBELAJARAN SNOWBALL THROWING BERBANTUAN MEDIA AUDIO PADA GURU SMAN 6 BALIKPAPAN UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA - Maryatin Maryatin; Mutiara Suci Rahmadhani; Laila Apriliana; Lilis Asriani Putri; Syntia Rizki Nur Safitri; Putri Ayu Megawati; Dwi Muklisum; Riski Novitasari; Swasti Maharani (Jurnal SOLMA, 2023)
Background: The active learning of students at SMAN 6 Balikpapan is still relatively low and needs to be improved. The purpose of this activity is to introduce the snowball throwing learning model to SMAN 6 Balikpapan teachers and its implementation in learning. Method: This socialization activity was carried out through four stages, namely planning, implementation, observation, and reflection. This socialization activity was attended by 20 teachers at SMAN 6 Balikpapan. After the presentation of the socialization material, a trial was carried out on 33 students in class XII IPA 5 in the Indonesian language subject. The instrument used in this trial was the student learning activity observation sheet. Results: The implementation results show that the application of the snowball throwing learning model is effective in increasing the learning activity of class XII IPA 5 SMA Negeri 6 Balikpapan in the subject of Indonesian novel material by 17.67%. So it can be said that the Snowball Throwing learning model can increase student learning activity in Indonesian subjects.